Perubahan Sosial-Ekonomi Masyarakat Petani di Sekitar Pelabuhan Perikanan Pantai Sadeng Gunung Kidul Daerah Istimewa Yogyakarta - Af’idatul Lathifah; Lydia Christianti (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
ONE – of the infrastructure development project was a port that has been done by the government of Indonesia, Sadeng Beach Fishery Port, in Girisubo District Gunung Kidul Regency, Yogyakarta. The emergence of ports in the area of Sadeng Beach Gunung Kidul brought changes to the community around Sadeng Beach area, considering the population in the area is not a fishing area. This research is an ethnographic research, within the researchers directly involved in various community activities in PPP Sadeng. Initially, the government brought fishermen from Gombong regency, Central Java to initiate the operation of the port. The construction of the harbor at Sadeng Beach is a government effort to improve the economy of the people around Sadeng Beach. However, the construction of ports in the middle of the farming community brings the consequences of socio-economic changes in the community around Sadeng Beach, especially the changes in the economic pattern of farmers to fisherman and the emergence of various types of fishermen in PPP Sadeng, the social cohesion changed among the community including the local fishermen with newcomers, and the emergence of new traditions.